Precursor Self‐Assembly Identified as a General Pathway for Colloidal Semiconductor Magic‐Size Clusters. Issue 12 (23rd October 2018) - Wang, Linxi; Hui, Juan; Tang, Junbin; Rowell, Nelson; Zhang, Baowei; Zhu, Tingting; Zhang, Meng; Hao, Xiaoyu; Fan, Hongsong; Zeng, Jianrong; Han, Shuo; Yu, Kui
Abstract: Little is known about the formation pathway of colloidal semiconductor magic‐size clusters (MSCs). Here, the synthesis of the first single‐ensemble ZnSe MSCs, which exhibit a sharp optical absorption singlet peaking at 299 nm, is reported; their formation is independent of Zn and Se precursors used. It is proposed that the formation of MSCs starts with precursor self‐assembly followed by Zn and Se covalent bond formation to result in immediate precursors (IPs) which can transform into the MSCs. It is demonstrated that the IPs in cyclohexane appear transparent in optical absorption, and become visible as MSCs exhibiting one sharp optical absorption peak when a primary amine is added at room temperature. It is shown that when the preparation of the IP is controlled to be within the induction period, which occurs prior to nucleation and growth of conventional quantum dots (QDs), the resulting MSCs can be produced without the complication of the simultaneous coproduction of conventional QDs. The present study reveals the existence of precursor self‐assembly which leads to the formation of colloidal semiconductor MSCs and provides insights into a multistep nucleation process in cluster science. Abstract : Precursor self‐assembly, with ZnSe as a model system is proposed as a general pathway for the formation of colloidal semiconductor magic‐size clusters (MSCs). The self‐assembly followed by ZnSe bond formation gives rise to the formation of immediate precursors of MSCs prior to formation of conventional quantum dots. ZnSe MSC‐299 forms from reactions of various Zn and Se precursors.